Emissions from railways: Results of tests on a pantograph-catenary test bench. (April 2023) - Fruhwirt, Daniel; Sturm, Peter; Bucca, Giuseppe; Bode, Gina; Michael, Sabrina; Rodler, Johannes
Abstract: Many railway tracks have been electrified, thus eliminating exhaust emissions. However, railways still emit particles due to abrasion and wear. The main such particle sources are brakes, wheel-rail contact, and pantographs and contact wire. However, information on the quantities of such particles is rare. Estimations in published data are quite heterogeneous, with PM10 emission levels varying by a factor of ten. In an attempt to improve the database and to reduce uncertainties, a series of test bench tests was conducted on pantograph-catenary contact. In order to study the impact of specific parameters, i.e. of train speed, contact force and current intensity, on the emitted particle mass and size distribution, parameter levels were varied across the tests. A chemical analysis of emitted particles provided information on the respective contributions of contact strip and contact wire. PM10 emission factors were found to lie in the range of 0.14–0.62 g/km.